Alga associated with diarrhea in patients with acquired immunodeficiency syndrome and in travelers. - Long, E G (1990)
Spherical bodies resembling coccidian oocysts and measuring 8.0 to 9.0 microns in diameter were seen in the stools of eight persons with explosive, watery diarrhea. Seven had recently traveled to tropical countries, mostly in the Caribbean, and four had acquired immunodeficiency syndrome. The structures were easily discernible in wet mounts by light microscopy and contained variable numbers of granular inclusions, but were refractory to, or stained partially with, 12 commonly used laboratory stains. Electron microscopy revealed an outer fibrillar coat, a thin cell wall, granules, and organelles which were not surrounded by membranes. One type of organelle was similar to the thylakoid photosynthesizing organelles of blue-green algae (cyanobacteria). These findings indicate that the bodies may be a species of blue-green algae.